CORRELATION OF VITAMIN D WITH LIPID PROFILE IN PATIENTS WITH CARDIO METABOLIC SYNDROME - Usman, Robina; Bibi, Yasmeen; Naheed, Rakshanda; Haq, Momina; Obaid, Seher; Khattak, Madiha (Journal of Postgraduate Medical Institute, 2020)
Objective: To find out the relationship between vitamin D and lipid profile in patients with cardio metabolic syndrome. Methodology: This case control study was carried out in Endocrinology Unit, Hayatabad Medical Complex from January to April 2012 on fifty adult patients of cardio metabolic syndrome. Controls were gender and age matched relatives of patients. Blood pressure, waist circumference, lipid profile, fasting blood sugar and serum 25-hydroxy vitamin D levels were recorded. Analysis of data was performed by SPSS version17. Results: A p value of <0.05 suggested a correlation of low vitamin D level with deranged lipid profile. Pearson correlation for TG and HDL was -.225 and 0.207 respectively. Linear regression between vitamin D and lipids depicted an inverse association between low vitamin D and TG (Î² coefficient =-0.225, p =0.024) and a direct association with HDL (Î² coefficient =0.207, p =0.039). Odds ratio for TG and HDL was 3.40 and 5.85 respectively inferring that low vitamin D may be a likely risk factor for cardio metabolic syndrome. Conclusions: low vitamin D level was found to be associated with high TG and low HDL.